Perbandingan antara Latihan Zig-Zag Run dan Shuttle Run Terhadap Kemampuan Dribbling pada Kegiatan Ekstrakurikuler Sepakbola SMA Negeri 2 Lubuklinggau - Arpansyah Arpansyah; Sukasno Sukasno; Wawan Syafutra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
Abstract This study aims to determine the difference in the effect of zig-zag run and shuttle run training on the dribbling ability of soccer extracurricular participants at SMA Negeri 2 Lubuklinggau. This study used an experimental method using two groups that received different treatments. Experimental group A with zigzag run treatment and experimental group B with shuttle run treatment. The population is all participants of the football extracurricular at SMA Negeri 2 Lubuklinggau totaling 20 people. The sampling technique was divided into two groups by simple random sampling. The research data collection used a soccer zig-zag dribbling test. The data analysis technique used the steps of normality test, homogeneity test, and t test. The results of the pretest data analysis tcount < ttable that is 1.894 <2.82 and all data are homogeneous. It can be concluded that Ho is accepted and Ha is rejected. The results of the post-test data analysis tcount > ttable that is 3.649> 2.82. The conclusion is that there is a significant difference in dribbling ability in soccer games between students who take part in the zig-zag run and shuttle run training in soccer extracurricular activities at SMA Negeri 2 Lubuklinggau. Keywords: Dribbling, Shuttle run, Soccer, Zig-zag run.